Facing Loss: Julie's Inner Struggle in Dustin Thao Novel’s You've Reached Sam - Ristan, Ghaisani Fakhrani (Universitas Ahmad Dahlan, 2024)
The inner conflict experienced by the character Julie in the novel You've Reached Sam by Dustin Thao and the way Julie's character overcomes inner conflict is interesting to study with the theory proposed by Kurt Lewin.This study aims to examine the inner conflict experienced by the main character in the novel You've reached Sam by Dustin Thao, along with the factors that affect the occurrence of these conflicts using a literary psychology approach. This research is a qualitative descriptive research with primary sources in the form of phrases, words, or sentences quoted in the novel You've reached Sam and secondary sources are used in the form of reference books, and national and international journal articles. The data collection technique is carried out by reading and recording data in the form of inner conflicts and the factors that affect them. The analysis technique in this study refers to the three stages of the triangulation technique. This research found that Juliet's character experiences an inner conflict that is in accordance with Kurt Lewin's formula are approach-approach conflict; avoidance-avoidance conflict; and approach-avoidance conflict. The dominant factors that affect the occurrence of inner conflicts are psychological pressure (driving forces) and tensions.